2016
DOI: 10.1002/jhet.2772
|View full text |Cite
|
Sign up to set email alerts
|

Indole‐Fused Epoxy‐1,5‐Diazocines as Cancer‐Selective Cytotoxic Agents

Abstract: Dimerization of 2‐(diformylmethylene)‐3,3‐dimethylindole by the action of tosyl chloride (TsCl) led to the creation of an epoxy‐[1,5]‐diazocine bicycle. The structure of the molecule resembles that of the naturally occurring C‐curarine‐I. The molecule shows significant cytotoxicity against cancer lines MCF‐7 and MDA‐MB‐231, but not toward the normal cell line CCD‐841. A series of substituted 2‐(diformylmethylene)‐3,3‐dimethylindoles was accordingly dimerized, and the products were studied for their cytotoxic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…Unfortunately, these structurally complex heterocycles are isolated in low yields (15a-d, 9-28%). In 2017, Khaledi and co-workers 22 employed a similar synthetic strategy (Scheme 4). Treatment of 1,3-dialdehyde 16 with NaOH and TsCl afforded epoxy [1,5][b,f]diazocines 17 in moderate to good yields, depending on the substitution pattern of the arene scaffold (17a-e, 54-86%).…”
Section: Short Review Synthesismentioning
confidence: 99%
“…Unfortunately, these structurally complex heterocycles are isolated in low yields (15a-d, 9-28%). In 2017, Khaledi and co-workers 22 employed a similar synthetic strategy (Scheme 4). Treatment of 1,3-dialdehyde 16 with NaOH and TsCl afforded epoxy [1,5][b,f]diazocines 17 in moderate to good yields, depending on the substitution pattern of the arene scaffold (17a-e, 54-86%).…”
Section: Short Review Synthesismentioning
confidence: 99%
“…Dibenzo [1,5]diazocines were first synthesised in 1896 1 and derivatives are categorised as eight-membered heterocycles comprising two nitrogen atoms at the 1,5-positions. These derivatives bear a close resemblance to Tröger's base which is of particular interest as a building block for supramolecular chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…
Dibenzo [1,5]diazocine scaffolds are present in a wide range of organic building blocks, for example in pharmaceuticals, materials and structural chemistry. However, the development of these structural frameworks has not received significant attention owing to limited synthetic protocols and strategies.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous examples of the use of 2-(3,3-dimethyl-3H-indol-2-ylidene)malondialdehydes for heterocycle construction. [6][7][8][9][10][11][12][13][14][15] Fused heterocycles containing pyrazolopyridine systems have been associated with several biological and medicinal activities. organic synthesis and numerous studies have been reported due to their well-documented biological activity.…”
Section: Introductionmentioning
confidence: 99%